REVIEW ARTICLESCIENTIFIC APPROACH IN LEARNING BASED ON THE 2013 CURRICULUM - ayu azzahra ayu (CV Grasta Glory, 2026)
The scientific approach is one of the approaches used in learning based on the 2013 Curriculum. This approach emphasizes the learning process that actively involves students through scientific activities such as observing, asking questions, gathering information, reasoning, and communicating. The purpose of this article is to examine the concept and application of the scientific approach in learning based on the 2013 Curriculum. The method used in writing this article is a literature study by reviewing various sources such as books, scientific journals, and articles relevant to the topic of discussion. The results of the study indicate that the application of the scientific approach can help improve student activity, critical thinking skills, and understanding of learning materials. In addition, this approach also encourages students to be more active in the learning process and is able to develop scientific skills. Thus, the scientific approach has an important role in improving the quality of learning in accordance with the objectives of the 2013 Curriculum.